Engineered composite fascia for stem cell therapy in tissue repair applications. (15th October 2015) - Ayala, Perla; Caves, Jeffrey; Dai, Erbin; Siraj, Layla; Liu, Liying; Chaudhuri, Ovijit; Haller, Carolyn A.; Mooney, David J.; Chaikof, Elliot L.
Graphical abstract: Abstract: A critical challenge in tissue regeneration is to develop constructs that effectively integrate with the host tissue. Here, we describe a composite, laser micromachined, collagen–alginate construct containing human mesenchymal stem cells (hMSCs) for tissue repair applications. Collagen type I was fashioned into laminated collagen sheets to form a mechanically robust fascia that was subsequently laser micropatterned with pores of defined dimension and spatial distribution as a means to modulate mechanical behavior and promote tissue integration. Significantly, laser micromachined patterned constructs displayed both substantially greater compliance and suture retention strength than non-patterned constructs. hMSCs were loaded in an RGD-functionalized alginate gel modified to degrade in vivo . Over a 7 day observation period in vitro, high cell viability was observed with constant levels of VEGF, PDGF-β and MCP-1 protein expression. In a full thickness abdominal wall defect model, the composite construct prevented hernia recurrence in Wistar rats over an 8-week period with de novo tissue and vascular network formation and the absence of adhesions to underlying abdominal viscera. As compared to acellular constructs, constructs containing hMSCs displayed greater integration strength (cell seeded: 0.92 ± 0.19 N/mm vs. acellular: 0.59 ± 0.25 N/mm, p  = 0.01), increased vascularization (cell seeded: 2.7–2.1/hpf vs. acellular: 1.7–2.1/hpf, p  < 0.03), and increased infiltration of macrophages (cell seeded: 2021–3630 μm 2 /hpf vs. acellular: 1570–2530 μm 2 /hpf, p  < 0.05). A decrease in the ratio of M1 macrophages to total macrophages was also observed in hMSC-populated samples. Laser micromachined collagen–alginate composites containing hMSCs can be used to bridge soft tissue defects with the capacity for enhanced tissue repair and integration. Statement of Significance: Effective restoration of large soft tissue defects caused by trauma or treatment complications represents a critical challenge in the clinic. In this study, a novel composite construct was engineered and evaluated for stem cell delivery and tissue repair. Laser micromachining was used to fabricate patterned, microporous constructs designed with pores of defined size and distribution as a means to tune mechanical responses, accommodate and protect incorporated cells, and enhance tissue integration. The construct was embedded within an engineered alginate gel containing hMSCs. Upon repair of a full thickness abdominal wall defect in a rat model, the composite construct modulated host innate immunity towards a reparative phenotypic response, promoted neovascularization and associated matrix production, and increased the strength of tissue integration.